Analysis Of The Effect Of The Work Environment And Compensation On Employee Performance at PT. Mentari Seraya Works - Sri Wahyuningsih; Harries Madiistriyatno; Aris Bayu Purnomo (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The objectives of this study are: 1) To determine the influence of the work environment on employee performance at PT. Mentari Seraya's work. 2) To determine the effect of compensation on employee performance at PT. Mentari Seraya's work. 3) To determine the effect of the work environment and compensation together on the performance of employees at PT. Mentari Seraya's work. This research is quantitative, descriptive and associative type. The population in this study were personnel serving in PT. Mentari Seraya's work. Regarding the research, the author used a simple random sampling technique, so the respondents that the author used were as many as 40 respondents, namely PT employees. Mentari Seraya's work. The results of this study show that: 1) There is an influence of the work environment on employee performance, as evidenced by the calculated t value for the Work Environment variable (X1) of 6,248 while table t value for N = 40 of 2,021. So 6,248 > 2.021, then H 0 is rejected and Ha is accepted, it can be stated that the Work Environment (X1) has a significant effect on Employee Performance (Y). 2) There is a peng a ruhkompensasi on employee performance, proven the calculated t value for the Compensation variable (X2) is 2,761, while the table t value for N = 40 of 2,021. So 2,761 > 2,021, then H 0 is rejected and Ha is accepted, it can be concluded that partially the Compensation variable (X2) affects Employee Performance (Y). 3) There is an influence of the work environment and compensation together on employee performance, as evidenced by the ANOVA obtained a calculated F value of 39.392 Medium Ftable (0.05) for N = 40 of 2.84. So Fcalculate the > of F of the table (0.05) or 39,392 > 2.84 with a significant rate of 0.000 because 0.000 < 0.05, then it can be said that Work Environment (X1) and Compensation (X2) together positively affect Employee Performance (Y). While the Adjusted R Square (R2) value is 0.680. This shows that 68% of the Work Environment (X 1) and Compensation (X2) simultaneously affect Employee Performance (Y) while the remaining 32% is influenced by other factors not studied in this study